INTESTINAL OBSTRUCTION WITH SUBMUCOSAL BOWEL LIPOMA - SANTOS, Daniel Costa (2023)
The digestive tract is an uncommon location for lipomas, but when present, they usually have their origin in the submucosa. Rarely, they can cause hemorrhage, intestinal obstruction and perforation. We report a case of a 79 year-old male presenting in the Emergency Department complaining of abdominal pain and vomiting for 2 days. Abdominal plain radiography was suggestive of intestinal obstruction. Computed tomography showed a jejunal obstruction. Laparotomy was performed and a mobile intra-luminal mass was identified and removed. Histology reported a submucosal lipoma. Submucosal lipomas are rare intestinal lesions. They most often occur on the colon, but can be present in any location of the gut. Lipomas can be sessile or pedunculated lesions and complications are mostly associated with lesions greater than 2cm. Surgical treatment can be an option.